Analysis of The Production Management of The Home Industry of Aria Chips in Sorong Regency, Southwest Papua Province, Indonesia - Nanulaitta, Yunita Abdin (Golden Ratio of Data in Summary, 2025)
Management is coordinating the resources owned by a company to achieve goals. According to Ricky W. Griffin, Management is a process of planning, organizational processes, coordination processes, and the process of controlling resources to achieve goals effectively and efficiently. However, based on facts in the field obtained from observations, there are several problems in the implementation of production management, namely, the direction function and the control function have not been running properly. This research was conducted at the Aria Chips Home Industry, Jl.Nusa Indah SP 2 Kelurahan. Of course, the district. Mariat Sorong Regency. The research method used is Qualitative Descriptive, namely researching the reality in the research field. Based on the research results, the application of home industry production management of Aria Usaha Chips has implemented five management functions per Ricky W. Griffin's theory. However, the implementation of production management has not run optimally because the direction and control section has not been carried out properly. The impact of the application of production management on the development of the home industry is the difficulty of obtaining raw materials for products; raw materials for Aria chips greatly affect the quality of the product.